ANALISIS KINERJA KEUANGAN PADA PT KERETA API INDONESIA TAHUN 2018-2022 - Saputri, Desi Maola Ayu (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
Trains have different characteristics from other modes of transportation, because they are able to accommodate more capacity, travel longer routes, and are more adaptive and provide adequate services for consumers. The company's financial condition reflects the company's financial condition and health. In 2020 and 2021 the company experienced losses due to the effects of the Covid pandemic. Analysis of PT KAI's financial performance using financial ratios, namely Current Ratio, Debt to Equity Ratio and Net Profit Margin. Data source sampling was carried out purposively and snowball. The collection technique was triangulation (combined), this research used a descriptive method with a quantitative case study design, namely PT KAI financial report data from 2018 to 2022. The results of this research are that in the period 2018 - In 2022, PT KAI's average current ratio will be 0.63 or 63%, meaning that the company is indicated to be having difficulty paying its obligations on time. The Solvency Ratio has a Debt to equity ratio value of more than 1, meaning the company's condition is in the healthy category. Financial performance as measured by the profitability ratio using the Net Profit Margin measuring tool means that PT Kereta Api Indonesia can be said to have good development in managing company profits.